Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1462-2920.2008.01689.x
|View full text |Cite
|
Sign up to set email alerts
|

Enriching plant microbiota for a metagenomic library construction

Abstract: Plant microbiota (the microorganisms that live in any associations with plant tissues) represents a rather unexplored area of metagenomic research compared with soils and oceans. Constructing a metagenomic library for plant microbiota is technically challenging. Using all the biomass without pre-enrichment could lead to vast proportions of the host plant DNA in the metagenomic library, doubtless obliterating the microbial contribution. Therefore, the first and essential step is to enrich for the constituent mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 22 publications
0
43
0
1
Order By: Relevance
“…Micromonosporaceae clade 1 is comprised of six endophytic strains isolated from plants on Mborokua Island and the uncultured bacterium clone 1-12D from the metagenomic library derived from Mallotus nudiflorus stem barks collected in Yunnan, China (42). Similar to clone 1-12D, all of our endophytic strains were isolated from either the stem bark of an unidentified tree or the prop root bark of a Pandanus sp., suggesting that this genus may specifically inhabit tissues outside of the vascular cambium.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Micromonosporaceae clade 1 is comprised of six endophytic strains isolated from plants on Mborokua Island and the uncultured bacterium clone 1-12D from the metagenomic library derived from Mallotus nudiflorus stem barks collected in Yunnan, China (42). Similar to clone 1-12D, all of our endophytic strains were isolated from either the stem bark of an unidentified tree or the prop root bark of a Pandanus sp., suggesting that this genus may specifically inhabit tissues outside of the vascular cambium.…”
Section: Discussionmentioning
confidence: 95%
“…Clade 1 also includes the uncultured bacterium clone 1-12D (accession number EU289478), which is the most closely related sequence in GenBank. Interestingly, the 16S rRNA gene of clone 1-12D is from the microbial-enriched DNA of the metagenomic library of the tree Mallotus nudiflorus (42 (2,4,34). Since the strains in clade 1 are equally related by sequence identity to the nearest type strains of three different genera and are all plant derived, they may represent a new genus in Micromonosporaceae.…”
Section: Isolation Of Strains and Distribution In Plant Tissuesmentioning
confidence: 99%
“…It was first successfully applied to the isolation of diverse endophytic actinobacteria from culture in our study. Recently, Wang et al (84) reported on the diversity of uncultured plant-associated microbes obtained by an improved DNA extraction method and increased differential centrifugation at a force of 5,000 ϫ g. Actinobacteria were the dominant microbial group, accounting for 37.7% of the 16S rRNA gene library, which also demonstrated the feasibility of using pretreatment method 3 for the isolation of endophytic actinobacteria.…”
Section: Resultsmentioning
confidence: 99%
“…3B and Table S4). Some references were derived from plant materials such as alpine shoots (47) and bark of the tropic tree Mallotus nudiflorus (54). The phylogenetic analysis revealed that Cluster I mainly including phyllosphereassociated Aurantimonas strains was phylogenetically distantly related to Cluster II mainly consisting of oceanassociated Aurantimonas strains (Fig.…”
Section: A Phyllosphere Cluster Of Aurantimonasmentioning
confidence: 99%